Effect of Thengtuk Dance Exercise on the Cognitive Function in the Elderly - Rongmuang, Daravan; Pauchpanpisan, Chuanchom; Nakchatree, Chantana; Tongdee, Jeraporn (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this quasi-experimental research was to examine the effect of Thengtuk dance exercise on the cognitive function in the elderly. A total of 30 participants were recruited using purposive sampling in each of the intervention and control groups. At the end of the study, the intervention group (n = 26) and control group (n = 28) continue in the study. The data collection tools composed of 1) intervention tools including a Thengtuk dance exercise for the elderly video and a guidebook for Thengtuk dance exercise for the elderly and 2) data collection tools including a demographic data questionnaire, The Mental Status Examination Thai, and the two-item depression screening. The data were analyzed using descriptive statistics, chi-square test, dependent t-test, and independent t-test. The results revealed that After participated in Thengtuk dance exercise, the mean difference in the cognitive function score between the intervention group and control group was higher than before statistically significant, but in the control group increased less than the intervention group (p < .001). When considering each component, there were significant differences in the mean score of language comprehension and language expression between the treatment and control group after the intervention (p = .02). There was no significant difference in other component.